PERBANDINGAN METODE SARIMA DAN METODE TRANSFER PADA PRODUKSI PADI DI KABUPATEN KENDAL - Safa'at Yulianto; Ahmad Jauharudin Najib (Politeknik Statistika STIS, 2020)
Indonesia is an agrarian country, meaning that agriculture holds an important role for the national economy. Based on data from the Central Statistics Agency in 2017 which states agriculture is one of the sectors that most contribute to the national economy with a contribution of 13.14 percent. In this agricultural sector, rice is the largest producer of production compared to other commodities with a production of 79 million tons in 2016. As a country with a large population, Indonesia faces challenges in meeting the needs of rice, but shifting the function of agricultural land to non-agriculture is very influential on yield rice production, the less land area, the less rice production is produced. No exception in Kendal Regency which has an agrarian area with the main commodity, rice, rice production in this Regency tends to decrease in 2016 and 2017. To assist the government in setting policies in food availability, forecasting analysis is used. The method most often used in forecasting is the ARIMA method. This method is actually quite good, but because rice production is also influenced by the area of ​​harvested land, a transfer function method is proposed that can include the harvested area variable in the forecasting model. The data used in this study are data on rice production and harvested area in Kendal Regency from January 2013 to December 2017. The test results using the transfer function forecasting method produce the best model